Covalent Affibody‐Molecular Glue Drug Conjugate Nanoagent for Proximity‐Enabled Reactive Therapeutics - Wenhui Gao; Xiaoyuan Yang; Qingrong Li; Yingchun Liu; Wei Huang; Xuelin Xia; Deyue Yan (Advanced Science)
Abstract Sulfur‐fluoride exchange (SuFEx) reaction is an emerging class of click chemistry reaction. Owing to its efficient reactivity under physiological conditions, SuFEx reaction is used to construct covalent protein drugs. Herein, a covalent affibody‐molecular glue drug conjugate nanoagent is reported, which can irreversibly bind with its target protein through proximity‐enabled SuFEx reaction. As a proof of concept, a latent bioreactive unnatural amino acid fluorosulfate‐L‐tyrosine (FSY) is first introduced at site 36 of the affibody with cysteine mutation (ZHER2:342‐Cys) to produce ZHER2:342‐36FSY‐Cys. Subsequently, ZHER2:342‐36FSY‐Cys is coupled with a molecular glue drug (CR8) to yield an amphiphilic conjugate of ZHER2:342‐36FSY‐CR8, which can self‐assemble into affibody–drug conjugate nanoagent (ZHER2:342‐36FSY‐CR8 ADCN) in PBS. When ZHER2:342‐36FSY‐CR8 ADCN specific binds to human epidermal growth factor receptor 2 (HER2) on cancer cells, the FSY36 of ZHER2:342 approaches to the His490 of HER2 and ultimately reacts with each other to form a covalent bond via SuFEx reaction. Such a covalent binding mode endows ZHER2:342‐36FSY‐CR8 ADCN with permanent binding ability to effectively increase the concentration of drugs in tumor. Eventually, the covalent ZHER2:342‐36FSY‐CR8 ADCN exhibits an outstanding tumor inhibition ratio of 90.03 ± 4.29% in HER2‐positive ovary tumor models, strikingly higher than that of the noncovalent one (64.25 ± 7.71%).